2012
DOI: 10.1371/journal.pone.0040662
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Sub-Cellular Shuttling of HTLV-1 Tax with the miRNA Machinery

Abstract: The innate ability of the human cell to silence endogenous retroviruses through RNA sequences encoding microRNAs, suggests that the cellular RNAi machinery is a major means by which the host mounts a defense response against present day retroviruses. Indeed, cellular miRNAs target and hybridize to specific sequences of both HTLV-1 and HIV-1 viral transcripts. However, much like the variety of host immune responses to retroviral infection, the virus itself contains mechanisms that assist in the evasion of viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 98 publications
0
30
1
Order By: Relevance
“…Given that we observed apoptosis in cells treated with purified VP40 protein and supernatants from cells transfected with VP40 DNA, we next asked whether Ebola VP40 was able to affect the cellular miRNA machinery of transfected cells, as well as cells receiving exosome-laden transfected cell supernatant treatments. It has been previously shown that some viruses interfere with host miRNA machinery as a means of evading host immune responses important for cell signaling and regulation of apoptosis (Coley et al, 2010; Van Duyne et al, 2012). Additionally, it has been observed that EBOV proteins VP35, VP30, and potentially VP40 are capable of deregulating the host RNAi pathway as suppressors of RNA silencing (Fabozzi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that we observed apoptosis in cells treated with purified VP40 protein and supernatants from cells transfected with VP40 DNA, we next asked whether Ebola VP40 was able to affect the cellular miRNA machinery of transfected cells, as well as cells receiving exosome-laden transfected cell supernatant treatments. It has been previously shown that some viruses interfere with host miRNA machinery as a means of evading host immune responses important for cell signaling and regulation of apoptosis (Coley et al, 2010; Van Duyne et al, 2012). Additionally, it has been observed that EBOV proteins VP35, VP30, and potentially VP40 are capable of deregulating the host RNAi pathway as suppressors of RNA silencing (Fabozzi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Infection with flaviviruses, including Dengue virus and Kunjin virus, has been previously shown to result in the inhibition of RNAi machinery and a downregulation of Drosha and DGCR8 (Moon et al, 2015; Casseb et al, 2016). We also have previously shown that the HTLV-1 protein Tax can directly modulate the RNAi pathway through the shuttling of Drosha and Dicer to the proteasome for degradation with no induction of apoptosis (Van Duyne et al, 2012). Alternatively, the downregulation of various miRNA machinery components including Dicer, Drosha, Exportin 5 and Ago proteins have, in many cases, been linked to the induction of apoptosis (Su et al, 2009; Han et al, 2013; Bian et al, 2014; Lombard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR181 modulates the T-cell antigen receptor sensitivity (44); miR150 regulates the transcription factor c-Myb13 and miR155 affects the differentiation of CD4 þ T lymphocytes into T helper type I (Th1) cells, regulatory T-cell development (45,46), and the promotion of T-cell-dependent tissue inflammation (46). HTLV-1 was previously shown to modify the pattern of miRNA expression in cell lines and ATLL samples (30)(31)(32)(33)(47)(48)(49)(50). Our results here add to these findings, as the miRNA expression profile of nonimmortalized infected T cells derived from carriers without malignancies was significantly distinct from that of uninfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic effects of Tax were previously thought to govern HTLV-1-associated miRNA dysregulation. By targeting Drosha to the proteasome, Tax influences global miRNA biogenesis (49). Furthermore, Tax activates the transcription of miR130b (33) and miR146a (32), and downregulates miR149 and miR873, which both directly target the chromatin-remodeling factors p300 and p/CAF that are known to play a critical role in HTLV-1 pathogenesis (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the HTLV-1 tax/rex mRNA maybe the target of cellular miRNAs (Hakim et al, 2008; Ruggero et al, 2010), which could lead to instability of this message. On the other hand, both Tax and Rex have been shown to interfere with the cellular microRNA machinery (Ruggero et al, 2010; Van Duyne et al, 2012), again suggesting potential positive feedback loops that would enhance tax/ rex mRNA stability.…”
Section: Discussionmentioning
confidence: 99%